Penerapan Relaksasi Autogenik Terhadap Penurunan Tekanan Darah Pada Pasien Hipertensi Di Bangsal Teratai RSUD dr. Soediran Mangun Sumarso Wonogiri - Devi Rohana Putri; Fida’ Husain; Sumardi Sumardi (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2024)
Background: Hypertension is one of the factors that is the main cause of death for stroke sufferers and is also a factor that can aggravate heart attacks. Non-pharmacological treatment usually includes exercise, improving diet and relaxing. Autogenic relaxation is relaxation that comes from oneself by using a word or sentence that calms a person's mind and is proven to be able to control several body functions such as blood pressure and blood flow. Objective: To determine the application of autogenic relaxation to reduce blood pressure in hypertension patients in the lotus ward at RSUD dr. Soediran Mangun Sumarso Wonogiri. Method: Autogenic relaxation with patients suffering from hypertension was carried out on 2 respondents for 3 days with a duration of 15-20 minutes and blood pressure was measured before and after application. Results: It was found that there was an effect of autogenic relaxation on reducing blood pressure in the blood pressure of respondents Mrs. W 215/109 to 177/96 and Mrs. N 173/100 to 158/92. Conclusion: Based on research that has been conducted, auogenic relaxation has been proven to be significant in reducing blood pressure in hypertension patients.